PEMBELAJARAN QUANTUM TEACHING DALAM PERSPEKTIF AL-QUR’AN Ahmad Nurcholis - Ahmad Nurcholis (Jurnal Pendidikan Islam, 2013)
This paper focuses on the discussion of quantum teaching learning model in the context of Islamic education that will be analyzed in the perspective of the Qur'an. Discussion of the method used is Tarbawi interpretation of Islam and science education. The results of the study showed that the quantum teaching is not new at all in Islam. At least the principles and steps of the learning process ever offered by the Qur'an. Problem is still poor for Muslims with the methodologies, and lazy in terms of research. Moreover, when examining the content of the Qur'an and Hadith. Al - Quran and al - Hadith only seen with one eye, which was then regarded as old-fashioned goods that it was time to saved become objects of history. The basic principles contained in the quantum teaching them Quran surah Al - Ahzab, 33: 72 , Al - Baqarah, 2: 21 , Ibrahim 14: 7 and Ar . Rahman, 55: 13, 16, 18, 21, 23, 25, 28, 30, 32, 34, 36, 38, 40, 42, 45, 47, 49, 51, 53, 55, 57, 59, 61, 63, 67, 69, 71, 73, 75, 77.